Islamic Financial Bank Performance in the World - Wardana, Guntur Kusuma; Masruroh, Sonia Ainun (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 3 No 1 (2022): Proceeding of International Conference on Engineering, Technology, and Social Sciences, 2023)
The purpose of this study was to partially analyze the effect of capital structure, bank size, and asset growth on the profitability (ROA) of Islamic banking in the world. The population in this study was 187 Islamic banks that were members of the IFSB in 2022. The type of research was quantitative with an explanatory approach. The sampling technique used purposive sampling with a total sample of 18 Islamic banks in the world. The results showed that the capital structure had a significant negative effect on profitability, while bank size had no significant effect on profitability. Asset growth has a significant positive effect on profitability.